2019
DOI: 10.1097/prs.0000000000005080
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Anatomy of the Deep Facial Fat Compartments: A Detailed Imaging-Based Investigation

Abstract: Background: Injection of soft-tissue fillers into the facial fat compartments is frequently performed to ameliorate the signs of facial aging. This study was designed to investigate the functional anatomy of the deep facial fat compartments and to provide information on the effects of injected material in relation to age and gender differences. Methods: Forty fresh frozen cephalic specimens of 17 male and 23 female Caucasian body donors (mean age, 76.9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
88
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 91 publications
(96 citation statements)
references
References 29 publications
3
88
1
4
Order By: Relevance
“…Recent studies have shown that over time fat is redistributed from subcutaneous locations such as the superficial and deep facial fat compartments to intra‐abdominal or ectopic locations such as the liver or the bone marrow . This supports the fatty deflation theory and explains the absolute (not relative) descent of some of the superficial and deep facial fat compartments with aging . Applying soft tissue filler can reflate the targeted facial fat compartments leading to restoration of volume.…”
Section: Introductionmentioning
confidence: 55%
“…Recent studies have shown that over time fat is redistributed from subcutaneous locations such as the superficial and deep facial fat compartments to intra‐abdominal or ectopic locations such as the liver or the bone marrow . This supports the fatty deflation theory and explains the absolute (not relative) descent of some of the superficial and deep facial fat compartments with aging . Applying soft tissue filler can reflate the targeted facial fat compartments leading to restoration of volume.…”
Section: Introductionmentioning
confidence: 55%
“…The cadaveric model, utilizing fresh, nonembalmed body donors, has provided previously reliable and clinically relevant results when investigating and validating various facial structures and procedures. This model was chosen in the past to describe the facial fat compartments, [34][35][36] facial danger zones, the pathophysiology behind injection-related visual compromises, 37,38 and when establishing the surfacevolume-coefficient, a novel parameter to describe soft tissue filler effectiveness. 29,32 However, the present study is the first to investigate the biomechanical effects of facial suspension threads in a cadaveric model.…”
Section: Discussionmentioning
confidence: 99%
“…Another structure of interest is the infraorbital nerve, which exits the infraorbital foramen and is thereafter enclosed in a fascial sheet together with the infraorbital artery and vein. 3 For a safe filler application, it is noteworthy that the medial border of the DMCF is formed by this fascial sheet. On the other hand, it should be taken into account that the angular vein forms the lateral border of the DMCF and the medial border of the DLCF.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, it should be taken into account that the angular vein forms the lateral border of the DMCF and the medial border of the DLCF. 3 Filler application into the superficial fat compartments using a cannula is relatively a safe procedure.…”
Section: Methodsmentioning
confidence: 99%